1974
DOI: 10.1029/ja079i007p01065
|View full text |Cite
|
Sign up to set email alerts
|

Observations of artificially produced scintillations using satellite transmissions

Abstract: The ionospheric modification experiment, utilizing a high‐powered transmitter located near Platteville, Colorado, provides an opportunity to study ionospheric irregularities under relatively known conditions. The irregularities were studied by means of transionospheric signals from the polar‐orbiting satellite Essa 8 transmitting at 137 MHz. These observations show that scintillations occur when the satellite to ground station geometry is such that the ray from the satellite passes through the region in the io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Such irregularities determine the anomalous attenuation of both the pump wave and the probing waves used for sounding the perturbed region of the ionosphere [1], as well as the intensity of aspect scattering of HF and VHF radiation [2,3]. Later, it was found that the generation of large-scale plasma-density irregularities is also more efficient at small angles between the wave vector of a high-power radio wave and the geomagnetic field [4,5]. Under conditions of "superrefraction" of high-power radio waves in the perturbed ionospheric region near their reflection altitude where the rays bend in such a way that the region of their reflection is confined in a narrow tube of the geomagnetic-field lines, very strong heating of a plasma and considerable variation in the plasma density are possible [6].…”
Section: Introductionmentioning
confidence: 99%
“…Such irregularities determine the anomalous attenuation of both the pump wave and the probing waves used for sounding the perturbed region of the ionosphere [1], as well as the intensity of aspect scattering of HF and VHF radiation [2,3]. Later, it was found that the generation of large-scale plasma-density irregularities is also more efficient at small angles between the wave vector of a high-power radio wave and the geomagnetic field [4,5]. Under conditions of "superrefraction" of high-power radio waves in the perturbed ionospheric region near their reflection altitude where the rays bend in such a way that the region of their reflection is confined in a narrow tube of the geomagnetic-field lines, very strong heating of a plasma and considerable variation in the plasma density are possible [6].…”
Section: Introductionmentioning
confidence: 99%
“…Immediately after highpower HF facilities became available at Platteville, Colorado •Utlaut, 1970] and at Arecibo, Puerto Rico [Gordon et al, 1971], not only were the temperature enhancements observed, as predicted by Farley, but a host of unexpected phenomena resulting from the nonlinear interaction of high-power radio waves with the ionospheric plasma were also detected [Carlson and Duncan, 1977;Guterich, 1978;Fejer, 1979, and references therein]. Among these varied phenomena, electron density variations at ionospheric heights were detected as manifested by artificial spread F on ionograms, radio star and satellite scintillations and enhanced incoherent scatter signals from the perturbed regions [Georges, 1970;Rufenach, 1973;Allen et al, 1974;Thorne and Perkins, 1974;Pope and Fritz, 1974;Getmantsev et al, 1976;Duncan and Behnke, 1978;Erukhimov et al, 1979;Belikovich et al, 1979;Basu et al, 1980Basu et al, , 1983Frey and Gordon, 1982;Livingston, 1983;Frey et al, 1984]. Later, density variations were measured directly by satellite in situ probes [Farley et al, 1983].…”
Section: Introductionmentioning
confidence: 99%